Improving Students’ TOEFL Score by Applying Discourse Strategies on TOEFL Listening Part A in Program Intensif Bahasa Asing (PIBA) of Universitas Islam Negeri (UIN) Alauddin, Makassar - Muhammad Syihab As'ad (Universitas Negeri Makassar, 2017)
This research was aimed to give an encouraging sight of students about reaching a good score on TOEFL. Then, this research facilitated the students to find the best way of increasing their TOEFL listening score in part A which is the focus of this research conducted in PIBA (Program IntensifikasiBahasaAsing) UIN Alauddin, Makassar. This research applied pre-experimental design. The data were collected from the subject which consist of 23 students. In the pre-test, there were only 22% who reach the good classification. After the treatment, the subjects’ score rose significantly by reaching 89% for good category. It was proven by the data of the mean score in pre-test was 392.61 while post-test got 445.65 for the mean score. The data indicated that the treatment gave slight increase in the research.Moreover, test of significant testing showed that the value of the t-table was higher than t-test.Through the interview, the researcher found that among all students, there were 54% used the sound-alike word, 38% applied the restatement idea, and only 8% used the most different option. Furthermore, this research revealed that the answer of TOEFL listening part A could be determined through intonation. The real situation of a conversation and speaker’s intention can be identified by the speaker’s intonation. Consequently, the findings and conclusions noted that the technique and strategies applied and revealed in this research were positively proposed. It is concluded that the students’ TOEFL score can slightly be increased by using discourse technique and by applying the strategies given in this research. Keywords: TOEFL score, discourse strategies, TOEFL listening part A, intonation.